Studying of Import Mechanisms for Different Length and Structure DNA into Plant Mitochondria - E.S. Klimenko (Journal of Stress Physiology & Biochemistry, 2014)
We investigated import of DNA of various length (109 bp, 269 bp, 717 bp, 1540 bp, 2732 bp, 9000 bp and 11600 bp) into the isolated mitochondria from potato tubers (Solanum tuberosum). The results imply existence of multiple pathways of DNA transfer into plant mitochondria. It was established that the transport of short length DNA (100-300 bp) is apparently carried out with the participation of several protein carriers which nature is currently unknown. We identified factors that influence the process of DNA transfer into mitochondria. These factors include the length of nucleic acid molecule and the presence of terminal inverted repeats that are specific to linear mitochondrial plasmids of plants.